FENOMENA URBAN SPIRITUALITAS SOLUSI ATAS KEGERSANGAN SPIRITUAL MASYARAKAT KOTA - Misbah, Mohammad (Fakultas Dakwah IAIN Purwokerto, 2011)
Modernity has given a great chance to modern people to meet and pursue their material needs in one hand, but on the other hand, they may lose the other essential need like happiness, peace of soul, self identity, and self meaning. They lose the